Educating the Next Generation : Improving Teacher Quality in Cambodia - Tandon, Prateek (Washington, DC: World Bank, 2014)
This book diagnoses Cambodian teaching quality and presents policy options for reform. Through classroom observation, assessments of mathematics and pedagogical content knowledge, and surveys of teachers and school directors, it sheds light on content and instruction, interactions with school directors, instructional support systems, and the implementation of teacher standards. The book investigates the competencies and skills of those attracted to teaching; it assesses the extent to which preservice education in Cambodia is delivering graduates with high content mastery and exposure to a student-centered learning environment; and it examines how teacher performance has been impacted by national incentives, an evaluation system that is disconnected from classroom realities, and the extent to which opportunities to learn and share best-practice lessons with peers exists. Out of the diagnosis follow three policy pillars to reform how teachers are trained, maintained, and motivated. First, the government must make teaching a much more attractive profession. Second, it must improve how teachers are prepared. And third, it must encourage stronger classroom performance. The book contains detailed recommendations under each policy pillar and provides the platform for Cambodia to undertake its next generation of educational reform.